Seed Yield and Quality of Late Season Direct Seeded Kenaf (Hibiscus cannabinus L.) as Influenced by Spacing and Time of De-topping - Mollah, Md. Abul Fazal; Rahman, Md. Moshiur; Zablul Tareq, Md.; Zahidul Hoque, ABM; Mehedi Hasan, Mir (The Agriculturists, 2017)
An experiment was conducted at the Bangladesh Jute Research Institute (BJRI), Regional Station, Kishoreganj during July to December of 2010 and 2011 to investigate the effect of spacing and de-topping on yield and quality of kenaf seeds cv. HC-95 grown under direct seeding method. Three plants spacings (40 cm × 15 cm, 30 cm × 15 cm and 20 cm × 15 cm) and four de-topping treatments (no de-topping, de-topping at 15, 30 and 45 days after emergence (DAE) were applied in a Randomized Complete Block Design (RCBD) with three replications. The highest yield of kenaf seed (1403 and 1646 kgha-1 in 2010 and 2011, respectively) was obtained from sowing at 30 cm × 15 cm spacing. The best quality seed in respect to germination and vigour was also obtained from sowing at 30 cm × 15 cm spacing. The highest seed yield, germination and vigour of seed were obtained for de-topped at 45 days after emergence. It is concluded that the highest seed yield and quality of late season direct seeded kenaf could be obtained by sowing at a spacing of 30 cm x 15 cm and de-topping at 45 days after emergence. The Agriculturists 2017; 15(1) 92-100